2017
DOI: 10.1093/bioinformatics/btx525
|View full text |Cite
|
Sign up to set email alerts
|

Orthologue chemical space and its influence on target prediction

Abstract: Motivation In silico approaches often fail to utilize bioactivity data available for orthologous targets due to insufficient evidence highlighting the benefit for such an approach. Deeper investigation into orthologue chemical space and its influence toward expanding compound and target coverage is necessary to improve the confidence in this practice.ResultsHere we present analysis of the orthologue chemical space in ChEMBL and PubChem and its impact on target prediction. We highlight the number of conflicting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
2

Relationship

5
5

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 25 publications
0
29
0
Order By: Relevance
“…A possible reason behind the low performance of the TFP descriptor models is that the protein targets from PIDGIN are of human origin, and are unlikely to provide a useful representation of target interactions in P. falciparum . However, it is the case that orthologous proteins exist between Homo sapiens and P. falciparum , and it has previously been shown that the number of conflicting bioactivities between human and ortholog targets in public databases is comparatively low (Mervin et al, 2018 ), which supports the use of human targets as bioactivity spectra in this indirect manner. It has also been shown that bioactivity spectra can be used more generally as a descriptor that captures biologically relevant information, and can outperform chemical descriptors in the identification of compounds with similar bioactivities [see Petrone et al (Petrone et al, 2012 ) Bender et al (Bender et al, 2006 ), Kauvar et al (Kauvar et al, 1995 ), Riniker et al (Riniker et al, 2014 ), and Paricharak et al (Paricharak et al, 2016 )].…”
Section: Resultsmentioning
confidence: 99%
“…A possible reason behind the low performance of the TFP descriptor models is that the protein targets from PIDGIN are of human origin, and are unlikely to provide a useful representation of target interactions in P. falciparum . However, it is the case that orthologous proteins exist between Homo sapiens and P. falciparum , and it has previously been shown that the number of conflicting bioactivities between human and ortholog targets in public databases is comparatively low (Mervin et al, 2018 ), which supports the use of human targets as bioactivity spectra in this indirect manner. It has also been shown that bioactivity spectra can be used more generally as a descriptor that captures biologically relevant information, and can outperform chemical descriptors in the identification of compounds with similar bioactivities [see Petrone et al (Petrone et al, 2012 ) Bender et al (Bender et al, 2006 ), Kauvar et al (Kauvar et al, 1995 ), Riniker et al (Riniker et al, 2014 ), and Paricharak et al (Paricharak et al, 2016 )].…”
Section: Resultsmentioning
confidence: 99%
“…To annotate the drugs in the database with their respective protein targets, we used the rat models available in PIDGIN version 2 50 on a per-compound bases. Previous benchmarking results have shown such in silico protocols perform with an average precision and recall of ~82% and ~83%, respectively, during fivefold cross validation 20 , hence giving a reasonable likelihood that compounds predicted to bind a particular target will indeed bind to this protein, or set of proteins.…”
Section: Methodsmentioning
confidence: 99%
“…This resulted in data for 327 protein targets, which we divided into five sub-classes: nuclear receptors, GPCRs, kinases, other enzymes, and ion channels. Inactive ligands were acquired from two sources: inactive ligands labeled on PubChem indexed by UniProt Protein ID (57,58) and for targets with a DUD-E decoy set, some inactives from the DUD-E set were included (59). To ensure a reasonable balance of actives to inactives, we also added a randomly selected set of 500 decoys per run; these decoy ligands were selected to not be in any previous set of ligands, either active or inactive.…”
Section: Methods and Data Availabilitymentioning
confidence: 99%